Peran Etos Kerja Islami, Gaya Kepemimpinan Transformasional dan Kecerdasan Emosional Terhadap Komitmen Organisasi - Munigar, Eni; Siti Maryam; Bellaji , Bismi Maryam; Pratiwi , Maudy Intan (CV. AFDIFAL MAJU BERKAH, 2024)
This study examines the influence of Islamic work ethic, transformational leadership style, and emotional intelligence on organizational commitment within the Al Bahjah Cirebon Formal Education Division. The population comprises all permanent teachers in the division, with a sample of 146 respondents selected for quantitative research. The data were collected via a questionnaire and analyzed using Smart PLS version 3.0. The findings indicate that an Islamic work ethic has a statistically significant impact on organizational commitment (t-statistic: 2.992, P-value: 0.003). Additionally, the transformational leadership style was found to have a positive effect on organizational commitment (t-statistic: 2.042, P-value: 0.042). 3) Emotional intelligence significantly contributes to organizational commitment (t-statistic: 2.251, P-value: 0.025). Collectively, these factors influence organizational commitment, with a coefficient of determination (R Square adjusted) indicating that they account for 30.2% of the variance. This suggests that while these three factors are important, 69.8% of the variance in organizational commitment is due to other variables not covered in this study.